User-friendly search interface for older adults: supporting search goal refreshing in working memory to improve information search strategies. Issue 10 (2nd October 2020) - Sanchiz, M.; Amadieu, F.; Paubel, P.-V.; Chevalier, A.
ABSTRACT: This study investigates how a search interface that displays users' ultimate query (i.e. users' current search goal) can cope with the age-related decrease of fluid abilities and support older users' search behaviours. 30 young and 18 older adults completed 9 search problems with a regular web browser or with the experimental search interface. Results showed that older adults spent longer time on the search engine result pages, they needed more time to reformulate, and they had more difficulties exploring the search paths elaborated. Age-differences also appeared as soon as the beginning of the search. The support tool helped older users reformulate their queries more rapidly and elaborate more flexible search strategies at the beginning of the activity. Indeed, older adults who interacted with the support tool switched to the processing of a new search path more rapidly instead of exploiting their initial query (i.e. they visited fewer websites for the initial query produced and reformulated a query instead of keeping on conducting a deeper investigation of the search results provided in the search engine result page). Implications of these findings for the design of effective support tools for older users are discussed.